The Impact of Transformational Leadership on the Development of Organizational Citizenship Behaviors in Educational Institutions in Oman: أثر القيادة التحويلية على تنمية سلوكيات المواطنة التنظيمية في المؤسسات التربوية في عمان - Mustahail, Amani Abdulghani Ramadhan Bait; Ahmad Sufian Che Abdullah; Ahmad Yussuf (Journal Al-Muqaddimah, 2025)
The aim of this research was to study the impact of transformational leadership on organizational citizenship behaviour. To achieve this, the researcher followed the descriptive-analytical approach on a sample appropriate to the research community, consisting of (200) male and female principals. This sample was selected using a deliberate random sampling method. The research tool was a special questionnaire after verifying its psychometric properties. The demographic variables were gender, academic qualifications, and years of experience. The independent variable was transformational leadership, while the dependent variable was organizational citizenship behavior. The study reached a set of results, including the impact of leadership styles and the impact of transformational leadership on organizational citizenship behaviors among second-cycle teachers in the Sultanate of Oman. The study also found that the degree of transformational Leadership practice was very high across all its dimensions (ideal influence, mental stimulation, individual consideration, and inspirational motivation). It was also found that there is an impact of transformational leadership on organizational citizenship behaviors among second-cycle teachers in the Sultanate of Oman, and that there are no statistically significant differences at the level (α=0.05) between transformational leadership and the level of The prevailing organizational citizenship behaviors among teachers in second-cycle schools in the Sultanate of Oman are attributed to the gender variable. It also showed that there are statistically significant differences at the level (α=0.05) between transformational leadership and the level of organizational citizenship behaviors among teachers in schools in the Sultanate of Oman, attributed to the variables of academic degree (bachelor’s) and higher years of experience.